Effectiveness of the rehabilitation for addicted prisoners trust (RAPt) programme. (August 2015) - Kopak, Albert M.; Dean, Lucy V.; Proctor, Steven L.; Miller, Lauren; Hoffmann, Norman G.
Abstract The Rehabilitation for Addicted Prisoners Trust (RAPt) Programme, the largest provider of intensive prison-based drug treatment in the UK, addresses both substance dependence and criminal behaviour through a comprehensive model. This study examined recidivism in a group of male prisoners who completed the RAPt programme (n = 352), a group of male prisoners who did not complete (n = 355) the programme, and a third comparison group of male prisoners who completed another in-prison drug treatment programme (n = 232). 12-month post-release recidivism data for the three groups were assessed with multivariate logistic regression in relation to age, race/ethnicity, length of sentence, prisoners' drugs of choice, and prisoners' primary offence for imprisonment. Results indicated that RAPt completers were less likely to re-offend within one year of prison release compared to the Comparison completers and prisoners who started but did not complete RAPt. Prisoners' drugs of choice were also associated with re-offence with those treated for heroin or cocaine (crack or powder) use being more likely to re-offend compared with those treated for use of any other drugs. Finally, the type of offence for which prisoners were convicted was also a prominent factor with those sentenced for a property offence more likely to reoffend within one year compared to those convicted of a non-property offence. These findings demonstrate the effectiveness of the RAPt programme and identify prisoners with heroin or cocaine dependence at highest risk for recidivism. Programme enhancements may address the additional risk among prisoners who identified heroin or cocaine use as their primary drug of choice.